ICE Thickness Using Ground Penetrating Radar at Znosko Glacier on King George Island - Bello, C. (2020)
Ground Penetrating Radar (GPR) survey was carried out to estimate the ice thickness and mapping the bedrock topography at Znosko glacier on King George Island, Antarctic Peninsula during 25 th Peruvian Antarctic Expedition (2018). GPR surveying did at 5.2 MHz frequency with a 16 m antenna gap (transmitter and receiver). The mean ice thickness profiles vary from 7 to 123 m across the 350 m profile length. This high-resolution survey also identified a different type of ices and glaciological features which will help in modelling the nature of the glaciers in the future.